Faktor-Faktor Yang Mempengaruhi Kinerja Usaha Mikro, Kecil Dan Menengah (UMKM) Di Kecamatan Narmada - Lalu Mulki Dewantara; Ida Ayu Nursanty; Elvina Setiawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have become a new economic force contributing to Indonesia's Gross Domestic Product (GDP). Currently, MSMEs have experienced a remarkable growth and contributed approximately 57% to Indonesia's GDP. This study aims to empirically examine the significant positive influence between independent variables, namely Capital (X1), Human Resources (X2), and Technology (X3), on the Performance of Micro, Small, and Medium Enterprises (SMMEs) (Y) in the Narmada District, West Lombok Regency. The research design employed in this study is associative research with a quantitative approach. The population consists of SMMEs in the Narmada District, West Lombok Regency. The sample was selected using probability sampling method, resulting in 88 formal MSMEs as the sample size. The data analysis was conducted using SPSS 25, employing classical assumption tests and multiple linear regression. The research findings indicate that capital has a significant positive influence on MSMEs' performance with a significance value of 0.003 < 0.05. Human resources have a significant positive influence on MSMEs' performance with a significance value of 0.001 < 0.05, and technology has a significant positive influence on MSMEs' performance with a significance value of 0.001 < 0.05.